Preparation method of activated carbon material with low-temperature electrochemical performance
By activating and calcining the activated carbon raw materials, adjusting the pore structure, and building a bimodal pore structure, the problem of the degradation of traditional activated carbon performance in low temperature environments is solved, excellent electrochemical performance at extremely low temperatures is achieved, and the preparation process is simplified to facilitate large-scale production.
Patent Information
- Application Number
- CN202311265940.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
In extreme low temperature environments, the performance of traditional commercial activated carbon electrodes rapidly declines, making it difficult to maintain capacity and rate performance similar to room temperature. The preparation process of existing low-temperature resistant electrode materials is complicated and is not suitable for large-scale production.
By activating and calcining the activated carbon raw material, adjusting its pore structure, increasing the mesoporous content, and building a bimodal pore structure (micro-mesoporous) to improve the transport kinetics of ions at low temperatures.
Excellent low-temperature performance is achieved at extremely low temperatures (-70°C), with almost no drop in room temperature compared to room temperature, significantly improving the low-temperature electrochemical performance of commercial activated carbon, and simplifying the preparation process to facilitate large-scale production.
Smart Images

Figure CN119724949A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing an activated carbon material with low-temperature electrochemical properties, and belongs to the field of supercapacitor electrode material preparation. Background Art
[0002] Energy storage devices with fast charge and discharge capabilities in extreme low temperature environments are essential for some low temperature application scenarios, such as high-altitude exploration, space missions, polar activities, and high altitude areas. Under such conditions, electric double-layer supercapacitors (EDLCs) are a very promising energy storage device. However, maintaining capacity and rate performance close to room temperature under extreme low temperatures remains a huge challenge. Currently, the performance of traditional commercial activated carbon electrodes usually decreases rapidly as the temperature decreases.
[0003] At present, the low-temperature resistant electrode materials reported in the literature are limited to small-scale laboratory preparation, and the preparation process is relatively complicated and cumbersome. This research is still in the basic research stage and is not suitable for large-scale production. For commercial activated carbon currently used in large quantities, there is a lack of reports on improving its low-temperature performance. Summary of the invention
[0004] According to one aspect of the present application, a method for preparing an activated carbon material with low-temperature electrochemical performance is provided, which can significantly promote the transport kinetics of ions at low temperatures and improve the transport of solvated ions at the solid-liquid interface and in the pores of porous carbon electrodes by activating and calcining the activated carbon raw material, adjusting its pore structure, increasing the mesopore content in the activated carbon, and constructing a bimodal pore structure. Excellent low-temperature performance can be achieved at extremely low temperatures (-70°C), which has important practical significance and is convenient for large-scale preparation and application.
[0005] The method for preparing the activated carbon material with low-temperature electrochemical performance comprises: calcining a mixture including an activation agent and an activated carbon raw material, washing and removing inorganic salt impurities to obtain the activated carbon material;
[0006] The activated carbon material has a bimodal pore structure;
[0007] The bimodal pore structure includes micropores and mesopores;
[0008] The pore size of the mesopores is 2 to 10 nm.
[0009] Optionally, the activated carbon raw material comprises a microporous structure;
[0010] In the activated carbon raw material, the pore diameter of the microporous structure is 0.5-2nm, and the pore volume of the micropores accounts for 60-90% of the total pore volume.
[0011] Optionally, the activated carbon material has a bimodal pore structure;
[0012] The bimodal pore structure includes micropores and mesopores;
[0013] The pore size of the mesopores is 2 to 10 nm.
[0014] Preferably, the pore size of the mesopores is 2 to 4 nm.
[0015] The pore size of the mesopores described in this application does not include 2 nm.
[0016] Optionally, the pore size of the mesopores is independently selected from any value of 2.5 nm, 3 nm, 4 nm, 6 nm, 8 nm, 10 nm, and a range of the above two values.
[0017] Optionally, the pore size of the micropores is 0.5-2 nm; preferably, the pore size of the micropores is 1-2 nm.
[0018] Optionally, the pore size of the micropores is independently selected from any value of 0.5 nm, 0.8 nm, 1 nm, 1.5 nm, 1.8 nm, 2 nm, and a range of the above two values.
[0019] Optionally, in the activated carbon material, the pore volume of mesopores accounts for 50-95%.
[0020] Optionally, in the activated carbon material, the pore volume proportion of the mesopores is independently selected from any value of 50%, 60%, 70%, 80%, 90%, 92%, 95% or a range of any two of the above.
[0021] Optionally, the activation reagent is any one or more of potassium hydroxide, zinc chloride, and phosphoric acid.
[0022] Optionally, the activated carbon raw material is YP50F and / or BC10 and / or other microporous carbon materials.
[0023] Optionally, the weight ratio of the activated carbon raw material to the activation agent is 1:(2-8); preferably, the weight ratio of the activated carbon raw material to the activation agent is 1:(4-7); more preferably, the weight ratio of the activated carbon raw material to the activation agent is 1:6.
[0024] Optionally, the weight ratio of the activated carbon raw material to the activation agent is independently selected from any value of 1:2, 1:4, 1:5, 1:6, 1:7, 1:8 or a range of the above two values.
[0025] Optionally, the calcination temperature is 600-1000°C, preferably, the calcination temperature is 700-900°C; further preferably, the calcination temperature is 800-900°C.
[0026] Optionally, the heating rate of calcination is 2-10°C / min; preferably, the heating rate of calcination is 3-7°C / min; further preferably, the heating rate of calcination is 5°C / min.
[0027] Optionally, during calcination, the insulation time is 1-6 hours; preferably, the insulation time is 1-4 hours; further preferably, the insulation time is 2-3 hours.
[0028] Optionally, the activated carbon raw material is dried before the mixture is calcined.
[0029] Optionally, the drying temperature is 50-150°C; preferably, the drying temperature is 80-120°C; further preferably, the drying temperature is 100°C.
[0030] Optionally, the drying time is 10-14 hours; preferably, the drying time is 11-13 hours; further preferably, the drying time is 12 hours.
[0031] In one embodiment, the preparation method of the activated carbon material with low-temperature electrochemical properties includes: taking activated carbon and an activating agent, grinding and mixing them evenly, transferring them to a crucible, and then transferring the crucible to a tubular furnace, sealing both ends of the tubular furnace, passing argon gas for a period of time, exhausting the air in the tubular furnace, heating to a specific temperature, keeping the temperature, cooling, and after the temperature cools to room temperature, taking out the sample in the tubular furnace, washing off the activating agent with dilute hydrochloric acid, and the activated carbon material can be obtained.
[0032] In the process of heat preservation and calcination in the present application, the activated carbon material reacts with the activation reagent, and part of the activated carbon material is etched away to form holes.
[0033] Another aspect of the present invention provides a capacitor electrode material slurry, which includes an activated carbon material prepared by the above-mentioned method for preparing the activated carbon material with low-temperature electrochemical properties.
[0034] Another aspect of the present invention provides a capacitor electrode, which is prepared from the activated carbon material prepared by the above-mentioned method for preparing the activated carbon material with low-temperature electrochemical properties.
[0035] Yet another aspect of the present invention provides a capacitor, comprising the capacitor electrode described above.
[0036] Optionally, the capacitor is an electric double layer capacitor.
[0037] Optionally, the minimum operating temperature of the double-layer capacitor can reach -100°C.
[0038] Optionally, the operating temperature of the double-layer capacitor is independently selected from any value among -70°C, -75°C, -80°C, -85°C, -90°C, -95°C, -100°C, -50°C, -25°C, 0°C, 25°C or a range between any two of the above.
[0039] The beneficial effects of this application include:
[0040] 1) The present application modifies the activated carbon raw material which is mainly microporous. The modified carbon material has a bimodal pore structure (micro-mesopores). When used in capacitor electrode materials, it can significantly promote the transport kinetics of ions at low temperatures, improve the transport of solvated ions at the solid-liquid interface and in the pores of porous carbon electrodes, and achieve excellent low-temperature performance at extremely low temperatures (-70°C). There is no significant decrease compared to room temperature, which greatly improves the problem of poor low-temperature electrochemical performance of currently used commercial activated carbon.
[0041] 2) The activated carbon material provided in this application has a simple and easy process and method, and is easy to scale up for production, facilitating large-scale and large-scale preparation of activated carbon materials in the later stage.
[0042] 3) The method of this application proposes for the first time to use chemical activation to adjust the pore structure of activated carbon, which is mainly micropores, to improve the low-temperature electrochemical performance. It is an effective method to improve the low-temperature performance of commercial activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 These are scanning and transmission electron microscope images of the modified commercial activated carbon in Example 1.
[0044] Figure 2 This is the XRD curve of the commercial activated carbon before and after modification in Example 1.
[0045] Figure 3 The physical adsorption-desorption and pore size distribution curves of the commercial activated carbon before and after modification in Example 1.
[0046] Figure 4 The electrochemical performance comparison of the commercial activated carbon before and after modification under extreme low temperature conditions (-70°C) in Example 4.
[0047] Figure 5 The low-temperature electrochemical performance of the electrochemical performance of the modified commercial activated carbon in Example 4, as well as the working voltage and energy density at low temperature.
[0048] Figure 6 The figure shows a comparison of the electrochemical performance of the commercial activated carbon before and after modification under low temperature conditions in Example 5. DETAILED DESCRIPTION
[0049] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0050] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0051] Example 1
[0052] After 1g of commercial activated carbon YP50F was vacuum dried in a vacuum oven at 100°C for 12h, it was ground and mixed evenly with 6g of potassium hydroxide, placed in a boat-shaped crucible, and transferred to a horizontal open tube furnace. Argon was introduced to exhaust the air in the tube furnace, and the air flow rate was set to 60ml / min. The heating program was set to heat to 800°C at a heating rate of 5°C / min and keep warm for 2h. After the tube furnace was cooled to room temperature, the activated sample was taken out to obtain the modified porous carbon material YP50F-800.
[0053] Figure 1 The scanning and transmission electron microscopy images of the modified commercial activated carbon in Example 1 are shown in Figure 1 (before: a, after: b). It can be seen from the figure that after modification, the carbon material produces a rich pore structure after activation.
[0054] Figure 2 The XRD curves of commercial activated carbon before and after modification prove that the degree of graphitization of the modified sample decreases.
[0055] Figure 3 The physical adsorption-desorption and pore size distribution curves of the commercial activated carbon before and after modification in Example 1. It can be seen from the figure that the modified carbon material produces a large number of mesopores at 2-4nm, and the pore volume of the mesopores accounts for 62%. At the same time, the micropore content at 1-2nm is also increased.
[0056] Example 2
[0057] After 1g of commercial activated carbon BC10 was vacuum dried in a vacuum oven at 100°C for 12h, it was ground and mixed evenly with 6g of potassium hydroxide, placed in a boat-shaped crucible, and transferred to a horizontal open atmosphere tube furnace. Argon was introduced for a period of time, and the air in the tube furnace was exhausted. The air flow rate was set to 60ml / min. The heating program was set to heat to 900°C at a heating rate of 5°C / min and keep warm for 2h. After the tube furnace was cooled to room temperature, the activated sample was taken out to obtain the modified porous carbon material BC10-800.
[0058] Example 3
[0059] In the glove box, use a measuring cylinder to measure 70 ml of methyl formate and 30 ml of acetonitrile to prepare 100 ml of mixed solvent. The above solvents have been treated to remove water. Weigh 11.73 g of SBP-BF 4The electrolyte is added to the above mixed solvent, stirred with a magnetic stirrer at room temperature for 4 h at a stirring speed of 500 rpm, and mixed evenly to prepare a low-temperature electrolyte with a concentration of 0.55 M.
[0060] Example 4
[0061] Weigh 88 mg of activated and modified carbon material YP50F-800 and unmodified YP50F, 4 mg of conductive agent (acetylene black), 4 mg of binder (sodium carboxymethyl cellulose), put them into agate grinder, grind the powder evenly, add 4 mg of styrene-butadiene rubber emulsion and 1 mL of water, grind to a slurry of a certain viscosity, apply it to the surface of carbon-coated aluminum foil with a scraper, transfer to an oven and dry overnight. Cut into discs of the same diameter with a slicer, assemble into symmetrical capacitor devices in a glove box, the electrolyte uses the low-temperature electrolyte prepared in Example 3, and the diaphragm is a polypropylene diaphragm of model 3501.
[0062] Example 5
[0063] Weigh 88 mg of activated and modified carbon material BC10-800 and unmodified BC10, 4 mg of conductive agent, and 4 mg of binder, grind the powder evenly in an agate grinder, add 4 mg of styrene-butadiene rubber emulsion and 1 mL of water, grind to a slurry of a certain viscosity, apply it on the carbon-coated aluminum foil with a scraper, transfer to an oven and dry overnight. Cut it into discs of the same diameter with a slicer, assemble it into a symmetrical capacitor device in a glove box, the electrolyte uses the low-temperature electrolyte prepared in Example 3, and the diaphragm is a polypropylene diaphragm of model 3501.
[0064] Test Example 1
[0065] The cyclic voltammetry curves of the assembled button device were tested at room temperature and low temperature using an electrochemical workstation CHI 760E. The integrated areas of the CV curves at room temperature and low temperature were compared to evaluate the electrochemical performance at low temperature.
[0066] Figure 4 The electrochemical performance comparison of the commercial activated carbon in Example 4 before and after modification under extreme low temperature conditions (-70°C).
[0067] Figure 5 The low-temperature electrochemical performance of the electrochemical performance of the modified commercial activated carbon in Example 4, as well as the working voltage and energy density at low temperature.
[0068] Figure 6 The figure shows a comparison of the electrochemical performance of the commercial activated carbon before and after modification under low temperature conditions in Example 5.
[0069] from Figure 4-6The electrochemical test results show that under the extreme low temperature environment of -70℃, the integral area of the CV curve of the modified commercial activated carbon almost coincides with that at room temperature, indicating that the electrochemical performance at low temperature has hardly decreased compared to that at room temperature, proving that the modified carbon material has excellent low-temperature electrochemical performance. In contrast, the low-temperature electrochemical performance of unmodified YP50F and BC10 is poor.
[0070] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing an activated carbon material having low-temperature electrochemical performance, characterized in that: include: calcining a mixture including an activation agent and an activated carbon raw material, and washing to remove inorganic salt impurities to obtain the activated carbon material; The activated carbon material has a bimodal pore structure; The bimodal pore structure includes micropores and mesopores; The pore size of the mesopores is 2 to 10 nm.
2. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: The activation reagent is selected from any one or more of potassium hydroxide, zinc chloride, and phosphoric acid; Preferably, the activated carbon raw material comprises a microporous structure; In the activated carbon raw material, the pore diameter of the microporous structure is 0.5-2nm, and the pore volume of the micropores accounts for 60-90% of the total pore volume.
3. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: The weight ratio of the activated carbon raw material to the activation agent is 1:(2-8).
4. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 3, characterized in that: The weight ratio of the activated carbon raw material to the activation agent is 1:(4-7).
5. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: The calcination temperature is 600-1000°C; Preferably, the calcination temperature is 700-900°C.
6. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: During calcination, the heating rate is 2-10°C / min; Preferably, the heating rate of calcination is 3-7°C / min.
7. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: During calcination, the holding time is 1-6h; Preferably, during calcination, the insulation time is 1-4 hours.
8. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: The pore size of the mesopores is 2 to 4 nm; Preferably, the pore volume of the mesopores accounts for 50-95%.
9. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 1, characterized in that: The pore size of the micropores is 0.5-2 nm.
10. The method for preparing an activated carbon material having low-temperature electrochemical performance according to claim 9, characterized in that: The pore size of the micropores is 1-2 nm.
Citation Information
Patent Citations
Active carbon for preparing carbon electrode of super capacitor and preparation method thereof
CN101844765A
Template-free preparation method of hierarchical porous active carbon electrode material
CN106744953A
Corncob-derived activated carbon electrode material and preparation method thereof
CN108046254A
Activated carbon material and preparation method thereof
CN108394899A
Hierarchical porous carbon material used for flexible supercapacitor and production method thereof
CN109850866A